2016
DOI: 10.1039/c6dt03515a
|View full text |Cite
|
Sign up to set email alerts
|

CO-releasing molecule (CORM) conjugate systems

Abstract: The development of CORMs (CO-releasing molecules) as a prodrug for CO administration in living organisms has attracted significant attention. CORMs offer the promising possibility of a safe and controllable release of CO in low amounts triggered by light, ligands, enzymes, etc. For the targeting of specific tissues or diseases and to prevent possible side effects from metals and other residues after CO release, these CORMs are attached to biocompatible systems, like peptides, polymers, nanoparticles, dendrimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 72 publications
(155 reference statements)
3
77
0
Order By: Relevance
“…The action of heme oxygenase (HO) on hemoglobin causes CO production in vivo and there is evidence that increased generation of HO‐derived CO plays a critical role in the resolution of inflammatory processes and alleviation of cardiovascular disorders . Due to these roles, CO has attracted much attention recently and there is a need to better understand its many biological functions, aiding the design of therapeutics using CO‐releasing molecules (CORMs) …”
Section: Resultsmentioning
confidence: 99%
“…The action of heme oxygenase (HO) on hemoglobin causes CO production in vivo and there is evidence that increased generation of HO‐derived CO plays a critical role in the resolution of inflammatory processes and alleviation of cardiovascular disorders . Due to these roles, CO has attracted much attention recently and there is a need to better understand its many biological functions, aiding the design of therapeutics using CO‐releasing molecules (CORMs) …”
Section: Resultsmentioning
confidence: 99%
“…Using a combination of spectroscopic techniques, theoretical calculations and multi‐curve resolution alternating least‐squares (MCR‐ALS) analysis, we have also demonstrated that the rate of decarbonylation is solvent dependent . Additionally, the feasibility to chemically link the Ru(II)‐based photoCORMs to delivery vectors without compromising on their CO‐releasing properties has also been demonstrated ,,. This offers interesting possibilities regarding the development of Ru(II) photoCORMs as site‐directed therapeutics.…”
Section: Introductionmentioning
confidence: 85%
“…These include CORMs that can be triggered for CO release using stimuli such as light (photoCORMs), enzyme activity (ETCORMs), or magnetic heating . For targeting purposes and/or to limit toxicity of the iCORM following CO release, metal carbonyl CORMs have also been incorporated into biocompatible structures such as proteins, polymers, dendrimers, and metal organic frameworks . Despite these advances, the majority of metal carbonyl CORMs reported to date cannot be tracked in terms of their cellular uptake and/or CO release process.…”
Section: Introductionmentioning
confidence: 99%